Casing Failure Characteristics, Prevention and Control Strate gies for Mature Oilfields. Issue 4 (May 2019) - Liu, Ying; Feng, Mingxi; Sun, Guoxin; Liu, Zheng; Ma, Cui; Zhong, Xiandong; Wang, Lisha; Liao, Ying
Abstract: As the oil and gas fields enjoy a longer and longer production life, casing damaged wells in oil and gas fields increase year by year in number. Assets are at expense, costs are incr eased, and production is threatened. In this paper, the status and mechanism of casing failures in China, USA and Russia are investigated; factors and prevention and intervention measures ar e analyzed; casing failure types, intervals, times and causing factors are studied; failure charact eristics and causes types of mature oilfields are compared and evaluated; and for each different-factor that causes casing failure a corresponding prevention or intervention method is suggested. The studies on casing failure mechanism, detection technology and modeling by overseas countries are worth of reference, and correlative technologies are significant guidance for casing failure prevention and control in our mature oilfields.